Posterior Reversible Encephalopathy Syndrome in an Infant Following Accidental Strangulation - Nandi, Madhumita; Sarkar, Sumantra (Journal of Pediatric Neurology, 2015)
Posterior reversible encephalopathy syndrome (PRES) (also called reversible posterior leukoencephalopathy syndrome) is a transient and reversible neurological disorder clinically characterized by seizures, blindness, and altered consciousness associated with radiological abnormalities especially in the posterior white matter. Hypertension has been implicated as the most common cause. Cerebral hypoxia has never been reported as a cause of infantile PRES. We describe one such case with the review of the literature.
Keywords: PRES; transient cerebral anoxia; accidental strangulation